Round ligament suspension and vaginal purse‐string suture: Newly optimized techniques to prevent tumor spillage in laparoscopic radical trachelectomy for cervical cancer. Issue 7 (10th May 2022) - Xu, Miaochun; Huo, Chuying; Huang, Chunxian; Liu, Yunyun; Ling, Xiaoting; Xu, Guocai; Lin, Zhongqiu; Lu, Huaiwu
Abstract: Aim: The purpose of this study was to investigate the surgical techniques and clinical feasibility of nonuterine manipulator and enclosed colpotomy to avoid cancer cell spillages in laparoscopic radical trachelectomy (LRT) for patients with early‐stage cervical cancer. Methods: We performed the newly optimized surgical techniques of round ligament suspension and vaginal purse‐string suture in LRT in 12 patients with early‐stage cervical cancer from May 2019 to October 2020. Surgical information and postoperative results were recorded. Results: All 12 patients successfully underwent LRT with round ligament suspension and vaginal purse‐string suture, and no conversion to laparotomy was required. The median operation time was 268.5 min (range 200–320 min), including 5 min of round ligament suspension, and the median blood loss was 20 mL (range 5–50 mL). The median number of pelvic lymph nodes removed was 27 (range 19–35), and median amounts of paracervical tissue was 24 mm (range 21–26 mm) and vaginal tissue was 18 mm (range 16–26 mm). No intraoperative complication or serious postoperative complications were reported. Conclusion: Round ligament suspension and vaginal purse‐string suture techniques are feasible and effective in LRT. They can replace uterine manipulator and unprotected colpotomy with satisfactory perioperative outcomes.